1991
DOI: 10.1080/00021369.1991.10870850
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Properties of Dipeptidyl Carboxypeptidase fromBacillus pumilus

Abstract: Enzymatic properties of dipeptidyl carboxypeptidase (DCP) from Bacillus pumilus were investigated. The enzyme was more active on tri- and tetrapeptides than angiotensin-converting enzyme (ACE) from rabbit lung. The presence of chloride ion is essential for the hydrolysis. The Km value of angiotensin I for the enzyme was 0.119 x 10(-3) M. The enzyme was not inhibited by the mammalian ACE inhibitors lisinopril and enalaprilat. The enzyme is readily inhibited by EDTA but restored by Co2+, Mn2+, and Zn2+. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Various compounds that might affect the activity of the purified enzyme were examined. Co 2 increased the specific activity about 3-fold, and this result resembles the case of the E. COU l5 ) and B. pumilus 20 ) enzymes (Table V). The Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Various compounds that might affect the activity of the purified enzyme were examined. Co 2 increased the specific activity about 3-fold, and this result resembles the case of the E. COU l5 ) and B. pumilus 20 ) enzymes (Table V). The Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 54%
“…These results show that the number of amino acid residues in peptide substrates seems to be important for the cleavage of the Pro-X bond. Angiotensin II and des-Arg9-bradykinin were not hydrolyzed because this enzyme did not cleave the imido bond, while mammalian ACE 30 ) and DCP from B. pumilus, 20) which have a tripeptidyl carboxypeptidase activity, cleave des-Arg9-bradykinin at the Phe-Ser bond and release Ser-Pro-Phe from the C-terminus. Various compounds that might affect the activity of the purified enzyme were examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the functional homology between captopril and β-lactams, ACE is an evolutionary highly conserved protein. DNA sequence analysis revealed that ACE-homologos could be identified in a variety of different eukaryotic phyla and in procaryotes [220][221][222][223][224][225][226][227]. Some of these ACE-like enzymes have been purified and biochemically characterized in vitro.…”
Section: Inhibitors Of Angiotensin-converting Enzyme and Other Zinc-cmentioning
confidence: 99%
“…The bacterial ACE-like enzymes from E. coli (EcDCP), Xanthamonas citri (XcACE), and dipeptidyl carboxypeptidases from Pseudomonas spp., P. maltophilia, Corynebacterium equi, B. subtilis and B. pumilus have retained their ability to hydrolyse angiotensin I, among other ACE substrates, and were inhibited by relevant ACE inhibitors. Sequence identities between the enzymes vary from 91 to 73% for XcACE and human N-ACE or ACE2, and 20-8% for EcDCP and the human enzymes, respectively [227][228][229]. Although the overall sequence similarity may be low in some cases, the active site is highly conserved, so that ACE-inhibitors inactivate the enzymes irrespective of their origin effectively.…”
Section: Inhibitors Of Angiotensin-converting Enzyme and Other Zinc-cmentioning
confidence: 99%